EnglishEducation on Making Liquid Fertilizer from Horse Urine at Berastagi Kuda Club - Ginting, Nurzainah; Mirwandhono, R. Edhy; Ginting, Armansyah; Masythah, Zuhrina; Rahim, Norizan Baba (ABDIMASKU : Jurnal Pengabdian Masyarakat UTND, 2025)
Horse urin that is not collected at the Berastagi Fruit Market and Gundaling tourist sites is a complaint for tourists. The urin splattered on the asphalt causes a strong odor. In this service, education was conducted to horse owners to collect horse urin and process it into liquid organic fertilizer (POC). Urin is collected from horses at tourist sites and in stables to maximize the volume of urin so that more POC is produced. The urin is then fermented by adding local starter. POC from fermented horse urin contains good nutrition so that it is suitable as a plant fertilizer. This International Community Service Program (PKM Kolaborasi Internasional) is a service collaboration between the Universitas Sumatera Utara and Universiti Sains Malaysia aims to provide education and training to the community on the use of horse urin to become liquid fertilizer. The activities were carried out through a participatory approach, including counseling, presentation of making urin fermentation, as well as pre-test and post-test evaluations to measure the increase in participant knowledge. The results of the activity showed that there was an increase in participant knowledge after participating in the activity, as well as high enthusiasm from the community for liquid fertilizer. There is an economic opportunity to sell liquid fertilizer to tourists who come because this fertilizer is environmentally friendly.